Protective Effect of Ginger Extract Against Cisplatin-Induced Hepatotoxicity and Cardiotoxicity in Rats. - Ahmed M. Attyah; Sajida H. Ismail (College of Pharmacy University of Baghdad, 2017)
The protective effect of ginger extract against cisplatin-induced hepatotoxicity and cardiotoxicity was evaluated in 30 albino white rats(weighing 200-300 gm ) classified into 5groups (6 rats per each group). The rats were treated with 0.5g/kg/day or 1g/kg/day ginger extract orally 5 successive days before and 5 successive days after induction of toxicity with intraperitoneal (IP) injection of (10mg/kg ) cisplatin, resulted in a significant reduction in the levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) , total serum  billirubin(TSB) , lactate dehydrogenase (LDH) and creatine kinase(CK) enzymes in comparison with the cisplatin treated animals; ginger extract also improves the histological changes produced by cisplatin in the liver cells and cardiac muscle fiber cells  in comparison with the control .  It is  concluded that , ginger extract when used concomitantly with cisplatin protects the liver and heart against the toxicity induced by this cytotoxic drug.                                         Key wards :Ginger, Cisplatin,Oxidative Stress